A Contemporary Meta-Analysis of Antegrade versus Retrograde Cerebral Perfusion for Thoracic Aortic Surgery - Takagi, Hisato; Mitta, Shohei; Ando, Tomo (The Thoracic and Cardiovascular Surgeon, 2019)
Objective To determine which of antegrade and retrograde cerebral perfusion (ACP and RCP) surpasses for a reduction in postoperative incidence of neurological dysfunction and all-cause death in thoracic aortic surgery, we performed a meta-analysis of contemporary comparative studies.Methods MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were searched from January 2010 to June 2017. For each study, data regarding the endpoints in both the ACP and RCP groups were used to generate odds ratios (ORs) and 95% confidence intervals (CIs). Study-specific estimates were combined using inverse variance-weighted averages of logarithmic ORs in the fixed-effect model.Results We identified and included 19 eligible studies with a total of 15,365 patients undergoing thoracic aortic surgery by means of ACP (a total of 7,675 patients) or RCP (a total of 7,690 patients). Pooled analysis demonstrated no statistically significant differences in postoperative incidence of stoke (17 studies enrolling a total of 9,421 patients; OR, 0.92; 95% CI, 0.79–1.08; p = 0.32) and mortality (16 studies including a total of 14,452 patients; OR, 1.07; 95% CI, 0.90–1.26; p = 0.46) between ACP and RCP, whereas a trend toward a significant reduction in incidence of temporary neurological dysfunction (TND) for ACP (12 studies enrolling a total of 7922 patients; OR, 0.85; 95% CI, 0.69–1.04; p = 0.12) was found.Conclusion In thoracic aortic surgery, postoperative incidence of stroke and mortality was similar between ACP and RCP, whereas a trend toward a reduction of TND incidence existed in ACP.
Keywords: antegrade cerebral perfusion; meta-analysis; retrograde cerebral perfusion